Endocrinology : pathophysiology to therapy - Quarde, Akuffo; Ohio Library and Information Network (Hoboken, NJ : Wiley-Blackwell, 2024)
Endocrinology: Pathophysiology to Therapy is a comprehensive resource on medical therapies; in each chapter, the relevant endocrine physiology of the medical therapy is presented, followed by a review of the detailed mechanism of action of selected medical interventions. Where applicable, emphasis is placed on clinical pharmacology pearls, such as side effects and therapeutic monitoring guidelines. Supplementary chapters address additional topics, including immune checkpoint inhibitor-related endocrinopathies, anabolic steroid abuse, pseudo-endocrine conditions, and dynamic tests in clinical endocrinology. Rather than emphasizing guideline-defined treatment protocols, this book directs attention towards the pathophysiology and fundamental principles of endocrine therapies
Pituitary gland therapies -- Thyroid gland therapies -- Adrenal gland therapies -- Pancreatic gland therapies -- Parathyroid gland and bone therapies -- Reproductive organ therapies -- Therapies in disorders of lipid metabolism and obesity -- Miscellaneous topics in disorders of endocrine glands -- Dynamic tests in clinical endocrinology
Includes bibliographical references and index
Keywords: Endocrinology; Endocrine System Diseases -- physiopathology; Endocrine Glands -- physiopathology; Endocrine System Diseases -- therapy